The prevalence of vitamin D deficiency and its association to modifiable risk factors of cardiovascular disease among apparently healthy adults in Central Kerala - Rose Mary Jacob Vatakencherry; Susan John; L Saraswathy; Renjitha Bhaskaran (Journal of Family Medicine and Primary Care)
Introduction: Cardiovascular diseases remain one of the leading causes of mortality globally with 80% occurring in developing countries. The known modifiable cardiovascular risk factors are Hypertension, Diabetes, Obesity, Hyperlipidaemia, Smoking, and Sedentary lifestyles. The prevalence of these risk factors is highest in Kerala (hypertension 30% and diabetes 14.8%). Globally India has the highest prevalence of cardiovascular disease especially in Kerala. The prevalence of vitamin D deficiency nationally is about 70–100% in some studies but shows contradictory results in various populations in Kerala (children 11% and 89% in perimenopause women). No Known study was done among apparently healthy adults in Kerala. Hence understanding its prevalence and its association if any to the cardiovascular risk factors may help to decrease the prevalence of cardiovascular disease. Methods: Subjects were taken from those who attended the health check-up at a tertiary hospital. Blood parameters like FBS, Triglyceride, High-Density Lipoprotein (HDL), and Serum Vitamin D were analyzed along with Blood pressure and waist circumference. Statistical Analysis: Frequency and Chi-squared test was done to look for prevalence and association of the various cardiovascular risk factors and vitamin D prevalence using IBM SPSS version 20.0 software. Result: It was found that Hypertension was highly prevalent (75%) among the cardiovascular risk factors. The prevalence of deficient and insufficient Vitamin D was 86.9% and it was significantly associated with Hypertension (p = <.001), Diabetes (p = <.001), High Triglycerides (p = <.001), and Low (at risk) High-density Lipoprotein (p = <.001) but not to obesity (P = 1.00). Conclusion: High prevalence of deficient and insufficient Vitamin D levels. And this was associated with all the risk factors except obesity. Additional information on low-density lipoprotein, Total Cholesterol, and HbA1c values would be strengthened. Further studies with supplementation preferably done in the community would help to confirm this association.